Pengaruh Budaya Organisasi, Kompetensi dan Motivasi Terhadap Kinerja Karyawan - Chairunnisa Sagala; Nadya Putri Mtd; Zainur Rozzaqiyah; Aulia Rahmi; Aldi Bayu Anggara; Chandra Wijaya (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Organizational culture is a pattern of behavior developed by an organization's employees learned when faced with problems of external adaptation and internal integration, that has proven good enough to be approved and taught to new members as a way to realize, think and feel. In addition, organizational culture refers to a system of shared meaning held by members that distinguishes the organization from other organizations. Organizational culture within an organization is usually associated with values, norms, attitudes and work ethic on hold in common by each component of the organization. If the culture of the organization will be able to improve both the high performance and will contribute to the company's success.